Diseño De Un Plan Integral De Control De Parásitos Gastrointestinales Para La Producción De Caprinos En La Granja San Pedro De La Universidad Antonio Nariño En La Localidad De Usme, Bogotá - Gómez Estepa, Paola Sofía; Parra Pulido, Laura Estefanía (Universidad Antonio Nariño, 2024)
This degree work was carried out with a population of goats from the USME farm of the UAN in Bogotá. This work will provide information about the most common gastrointestinal nematodes in goats, performing a detailed bibliographic review of each one. In addition, the results of general examinations performed on the animals, such as FAMACHA and coproscopic examinations, will be included. Based on these findings, a comprehensive parasite control management will be proposed, focused specifically on the farm, but which can also be applied to any other farm in general.